UJI EFEKTIFITAS E-MODUL TRIGONOMETRI BERBASIS SCHOOLOGY UNTUK PEMBELAJARAN DARING DI POLITEKNIK - I Gde Nyoman Sangka (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Unmas Denpasar, 2021)
The purpose of the study was to determine the level of validity, practicality, and effectiveness of the E-Module Trigonometry. The research uses the ADDIE model development research approach with stages: Analysis, Design, Development, Implementation, and Evaluation. The implementation is in the Department of Electrical Engineering, Bali State Polytechnic. Data were collected using a validation questionnaire, practicality questionnaire, pretest and posttest of trigonometric competence. Validation includes aspects: content feasibility, presentation, language, and graphics carried out by experts and practitioners. Practicality through trials: small groups, large groups and limited trials. The subjects are students and mathematics lecturers. Effectiveness through t test data pretest and posttest in the experimental and control groups. The subject is student. The data were analyzed descriptively, the results showed the level of validity reached 81.9%, categorized as valid. The level of practicality through practicality tests by lecturers is 82.0% which is categorized as practical with minor revisions and the level of practicality through practical tests by students is 81.8% categorized as practical with minor revisions. The results of the independent sample test showed that there was a significant difference (sig.0.000) between learning outcomes using e-modules and without e-modules. The results of the paired t test of the experimental group showed the correlation coefficient between the initial ability (before) and the final ability (after) the learning process with the E-Module of 0.707 categorized as positive, strong and significant. Thus, the E-Module is declared feasible, practical, and effectively used as teaching material.